2016
DOI: 10.1111/trf.13968
|View full text |Cite
|
Sign up to set email alerts
|

Additional intraarticular tranexamic acid further reduced postoperative blood loss compared to intravenous and topical bathed tranexamic acid in total hip arthroplasty: a retrospective sequential series study

Abstract: This study suggests that the combined administration of topical intraarticular, bathed, and IV TXA was effective in reducing blood loss in THA patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
1
2
0
Order By: Relevance
“…[30] In addition to the IV TXA, the combined IA TXA was suggested effective in reducing blood loss in total hip arthroplasty. [31] Moreover, in line with our study, the IV plus IA TXA treatment was revealed to have a 37% reduced blood loss compared with IV TXA-alone at 24 and 48 hours after TKA, where no thromboembolic complications occurred. [32] Additionally, the inhibitory effect of TXA on the fibrinolytic activity was previously demonstrated in several studies.…”
Section: Discussionsupporting
confidence: 82%
“…[30] In addition to the IV TXA, the combined IA TXA was suggested effective in reducing blood loss in total hip arthroplasty. [31] Moreover, in line with our study, the IV plus IA TXA treatment was revealed to have a 37% reduced blood loss compared with IV TXA-alone at 24 and 48 hours after TKA, where no thromboembolic complications occurred. [32] Additionally, the inhibitory effect of TXA on the fibrinolytic activity was previously demonstrated in several studies.…”
Section: Discussionsupporting
confidence: 82%
“…The efficacy of TXA in reducing blood loss and transfusion requirement has been confirmed in numerous studies but there has been debate regarding the best route of administration . Several studies have compared the efficacy of topical and intravenous administration of TXA, and others have compared the efficacy of combined administration versus intravenous or topical TXA in primary THA . While routes of TXA administration have been compared for total knee arthroplasty by our own group, few studies have directly compared the three routes in THA.…”
Section: Discussionmentioning
confidence: 99%
“…15,27 Several studies have compared the efficacy of topical and intravenous administration of TXA, 28,29 and others have compared the efficacy of combined administration versus intravenous or topical TXA in primary THA. 19,30 While routes of TXA administration have been compared for total knee arthroplasty by our own group, 31 few studies have directly compared the three routes in THA. In addition, concerns still exist about the safety of TXA in primary unilateral THA.…”
Section: Discussionmentioning
confidence: 99%